1977
DOI: 10.4269/ajtmh.1977.26.171
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Western Equine Encephalitis Viremia in the Texas Tortoise (Gopherus Berlandieri)

Abstract: Subcutaneous inoculation of 34 Texas tortoises (Gopherus berlandieri) with either of two strains of Western Equine Encephalitis (WEE) virus resulted in prolonged viremia of up to 105 days' duration. Peak viremia titers exceeded 10(6) suckling mouse intracranial lethal doses per milliliter. The length of the previremic period, the maximum viremia level attained, and the duration of viremia were markedly affected by environmental temperature. Higher temperatures (30 degrees C) shortened the previremic period and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Because of their relatively low body temperatures and inefficient antibody responses, 14 ectotherms can support prolonged viremias compared with birds and mammals, 15 and previous laboratory studies have suggested a role for ectotherms as overwintering hosts for arboviruses. [20][21][22] These studies suggest that ectotherms may represent an over-looked reservoir host, and perhaps an important over-wintering refuge for EEEV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of their relatively low body temperatures and inefficient antibody responses, 14 ectotherms can support prolonged viremias compared with birds and mammals, 15 and previous laboratory studies have suggested a role for ectotherms as overwintering hosts for arboviruses. [20][21][22] These studies suggest that ectotherms may represent an over-looked reservoir host, and perhaps an important over-wintering refuge for EEEV.…”
Section: Discussionmentioning
confidence: 99%
“…This feature may be especially true of EEEV because it is found in hardwood swamps where amphibians and reptiles are particularly abundant. 1 In addition, the prolonged viremia observed in experimentally infected reptiles relative to what is found in mammals and birds 14,15 may lead to an increased probability of transmission to mosquitoes. Scattered studies indicate that some ectothermic hosts potentially serve as competent reservoirs for arboviruses, [15][16][17][18][19][20] and support their potential role as over-wintering hosts for arboviruses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A report of prolonged infection of birds by western equine encephalitis virus for as long as 234 days (256) generated interests. Other examples of long-term infections include bluetongue virus infection in cattle that lasted as long as 100 days, Omsk hemorrhagic fever virus infection in water voles for 155 days, and western equine encephalitis virus infection in tortoise for 105 days (28,150,165,195). More recently, it was reported that WNV was shed in urine by infected golden hamsters for 8 months (312).…”
Section: Viremia Nonviremic Transmission and Long-term Infectionmentioning
confidence: 99%
“…in the laboratory 15,16 and can persist for prolonged periods in the Texas tortoise ( Gopherus berlandieri ). 17 EEEV has also been recovered from a number of wild ectotherms, 18,19 while alligators have been implicated as potential amplifying hosts for West Nile virus. 20 These studies suggest that ectothermic hosts might serve as reservoir hosts for EEEV, and may provide a mechanism for overwintering in some areas or transmission foci of the virus.…”
Section: Introductionmentioning
confidence: 99%